Prophecy, past and present an exploration of the prophetic ministry in the Bible and the church today - Hill, Clifford S. (Highland Highland Books, 1989)
A study of the nature and purpose of prophecy both as a means of revelation in biblical times and as a spiritual ministry today, this book should also help readers to distinguish between true and false prophets - to "discern the spirits", in a biblical phrase.
Keywords: Prophecy -- Christianity. Christian doctrine -- Prophecy